2019
DOI: 10.1039/c9nj00180h
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of 99mTc-MBIP-X/11[C] MBMP for visualization of 18 kDa translocator protein

Abstract: An elevated translocator protein (18 kDa, TSPO) density is observed during inflammation in the brain and peripheral organs making it a viable target for imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The in vivo and ex vivo biodistribution analysis on chloro derivative of MBIP showed a seven-fold higher uptake in heart and 2.5-fold enhanced uptake by heart, and 2.5-fold increased uptake by the lungs as compared to the bromo derivative. [87] Fujinaga et al reported the synthesis of 18 F-labeled radiotracers 104-109 (Figure 25) with improved brain kinetics for PET imaging of TSPO in the glioma and ischemic brain. Bromobenzoxazolone acetic acid 102 (Figure 25) was reacted with 2-methylaminopyridine, N-methylaniline, and 4-methylaminopyridine in the presence of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (WSC) and hydroxybenzotriazole (HOBt) to procure the final acetamidobenzoxazolones.…”
Section: Translocator Protein (Tspo) Inhibitorsmentioning
confidence: 99%
“…The in vivo and ex vivo biodistribution analysis on chloro derivative of MBIP showed a seven-fold higher uptake in heart and 2.5-fold enhanced uptake by heart, and 2.5-fold increased uptake by the lungs as compared to the bromo derivative. [87] Fujinaga et al reported the synthesis of 18 F-labeled radiotracers 104-109 (Figure 25) with improved brain kinetics for PET imaging of TSPO in the glioma and ischemic brain. Bromobenzoxazolone acetic acid 102 (Figure 25) was reacted with 2-methylaminopyridine, N-methylaniline, and 4-methylaminopyridine in the presence of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (WSC) and hydroxybenzotriazole (HOBt) to procure the final acetamidobenzoxazolones.…”
Section: Translocator Protein (Tspo) Inhibitorsmentioning
confidence: 99%
“…Conventionally, the earliest TSPO ligand was benzodiazepine [ 11 C]-Ro5–4864 that differentiated peripheral and central benzodiazepine receptors . Diverse TSPO ligands from various structural classes such as isoquinoline carboxamides (e.g., [ 11 C]-PK-11195, [ 11 C]-ER176), benzodiazepines (e.g., [ 11 C]-Ro5–4864), phenoxyarylacetamides (e.g., [ 11 C]-DAA1106), aryloxyanilides (e.g., [ 11 C]-PBR28), 2-phenyl-imidazo­[1,2- a ]­pyridine acetamides (e.g., alpidem), and pyrazolopyrimidines ([ 18 F]-DPA-714) have been described. Figure encloses famously used first-, second-, and third-generation ligands. Besides different endogenous biomolecules such as cholesterol or compound porphyrin, TSPO exhibits binding to a range of synthetic ligands.…”
Section: Tspo Pet Tracers-current Statusmentioning
confidence: 99%
“…The visualization of overexpressed microglial cells in the living brain by high affinity and selective PET tracers has been considered as a powerful tool for staging the neuroinflammation. 22 , 23 The development of PET tracers was initially started in the mid-1980s using positron emitter isotopes 11 C and 18 F. 24 PET tracers have much potential for in vivo molecular imaging and play a most impressive role for the assessment and staging of neuroinflammation. 25 PET tracers of TSPO have been categorized in three generations, which are presented in Figure 3 .…”
Section: Introductionmentioning
confidence: 99%